2012
DOI: 10.1017/s0029665112000730
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of macrophage migration inhibitory factor in obesity and insulin resistance

Abstract: High-fat diet (HFD)-induced obesity has emerged as a state of chronic low-grade inflammation characterised by a progressive infiltration of immune cells, particularly macrophages, into obese adipose tissue. Adipose tissue macrophages (ATM) present immense plasticity. In early obesity, M2 anti-inflammatory macrophages acquire an M1 pro-inflammatory phenotype. Pro-inflammatory cytokines including TNF-α, IL-6 and IL-1β produced by M1 ATM exacerbate local inflammation promoting insulin resistance (IR), which conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 138 publications
(224 reference statements)
3
55
0
2
Order By: Relevance
“…While 3T3-L1 cells were grown to confluence, cells were stimulated by differentiation medium consisting of 10% FBS, 0.5 mM 3-isobutyl-1-methylxanthine (IBMX), and 1 μM dexamethasone (DEX) and incubation for 8 days and then insulin (10 μg/mL) was added at the last 2 days, at which time infiltration of macrophages in adipose tissue, releasing numerous pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α), and interleukins, which consequently contributed to progressive exacerbation of insulin resistance and eventually, metabolic syndrome [12,13].…”
Section: Culture and Differentiation Of 3t3-l1 Cellsmentioning
confidence: 99%
“…While 3T3-L1 cells were grown to confluence, cells were stimulated by differentiation medium consisting of 10% FBS, 0.5 mM 3-isobutyl-1-methylxanthine (IBMX), and 1 μM dexamethasone (DEX) and incubation for 8 days and then insulin (10 μg/mL) was added at the last 2 days, at which time infiltration of macrophages in adipose tissue, releasing numerous pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α), and interleukins, which consequently contributed to progressive exacerbation of insulin resistance and eventually, metabolic syndrome [12,13].…”
Section: Culture and Differentiation Of 3t3-l1 Cellsmentioning
confidence: 99%
“…MIF is released from cells through a nonconventional protein-secretion pathway [8]. It is involved in immunological and inflammatory diseases [9,10] such as chronic diseases including bowel disease [11], obesity [12,13], and diabetes [14]. More recently, MIF was proposed as a diagnostic biomarker for autoimmune diseases such as diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most critical functions of MIF encompass the regulation of macrophage and lymphocyte activation in innate and adaptive immune responses, respectively [13], and its gene has been identified as a novel candidate gene for T2D. Several lines of evidence support a relationship between MIF and T2D [14,15]. Studies have demonstrated that MIF may play a key role in regulating glucose by altering insulin secretion [13].…”
Section: Introductionmentioning
confidence: 99%